The presence of physician champions improved Kangaroo Mother Care in rural western India. (16th May 2016) - Soni, Apurv; Amin, Amee; Patel, Dipen V.; Fahey, Nisha; Shah, Nikhil; Phatak, Ajay G.; Allison, Jeroan; Nimbalkar, Somashekhar M.
Abstract: Aim: This study determined the effect of physician champions on the two main components of Kangaroo Mother Care (KMC): skin‐to‐skin care and breastfeeding. Methods: KMC practices among a retrospective cohort of 648 infants admitted to a rural Indian neonatal intensive care unit (NICU) between January 5, 2011 and October 7, 2014 were studied. KMC champions were identified based on their performance evaluation. We examined the effect of withdrawing physician champions on overall use, time to initiation and intensity of skin‐to‐skin care and breastfeeding, using separate models. Results: In comparison with when KMC champions were present, their absence was associated with a 45% decrease in the odds of receiving skin‐to‐skin care, with a 95% confidence interval (CI) of 64% to 17%, a 38% decrease in the rate of initiation skin‐to‐skin care (95% CI 53–82%) and an average of 1.47 less hours of skin‐to‐skin care (95% CI −2.07 to −0.86). Breastfeeding practices were similar across the different champion environments. Conclusion: Withdrawing physician champions from the NICU setting was associated with a decline in skin‐to‐skin care, but not breastfeeding. Training health care workers and community stakeholders to become champions could help to scale up and maintain KMC practices.